(untitled) (Journal of Pedagogi, 2024)
The transformation of education management in the digital era has changed the paradigm of education management and implementation by utilizing technology to improve quality and efficiency. This study aims to explore strategic innovations in education management based on digital technology, including the digitalization of administration, learning and human resource development. The research method uses a qualitative approach with a descriptive design to analyze the transformation of education management in the digital era. The results show that digitalization has simplified administrative processes, increased student engagement through interactive learning platforms, and reduced education operational costs. In addition, technology-based training significantly improves teachers’ competence in using digital tools, which has a positive impact on learning effectiveness. However, challenges such as the digital divide and resistance to change remain major obstacles that need to be overcome. The transformation of education management in the digital era has presented great opportunities to improve the quality and efficiency of education through strategic innovation. The implications of this study emphasize the importance of policy support for equitable access to technology, strengthening teacher training and increasing collaboration through digital platforms to create an inclusive and sustainable education ecosystem.